Noninvasive Evaluation of Flow Reserve in the Left Anterior Descending Coronary Artery in Patients With Cardiac Syndrome X - Galiuto, Leonarda; Sestito, Alfonso; Barchetta, Sabrina; Sgueglia, Gregory A.; Infusino, Fabio; La Rosa, Claudio; Lanza, Gaetano; Crea, Filippo (The American journal of cardiology, 2007)
Data on coronary flow reserve (CFR) in patients with syndrome X are still controversial. Further, noninvasive evaluation of epicardial and microvascular flow reserves in these patients has never been performed. In 17 patients with syndrome X and in 17 age- and gender-matched control subjects, CFR in the mid left anterior descending coronary artery (LAD) was evaluated by transthoracic color and pulse-wave Doppler using a 7-mHz probe (Sequoia, Siemens). Peak diastolic LAD flow was calculated at rest and at peak adenosine (140 μg/kg/min intravenously in 90 seconds). Myocardial contrast echocardiography (MCE) was performed at rest and during adenosine use by real-time cadence pulse sequencing and intravenous SonoVue (Bracco; 5 ml at 1 ml/min) and microvascular blood volume (A), velocity (β), and flow (A×β) by replenishing curves (y = A[1 − e βt]). CFR was measured by Doppler echocardiography as an adenosine/rest velocity ratio and by MCE as a microvascular volume, velocity, and flow adenosine/rest ratio. Compared with controls, patients with syndrome X demonstrated lower LAD CFR and velocity and flow microvascular flow reserves (p <0.01, <0.005, and <0.005, respectively). In patients with syndrome X, those with angina and ST-segment depression during adenosine testing had even lower LAD CFR and velocity and flow microvascular flow reserves compared with those with no symptoms (p <0.0001, <0.0001, and <0.005, respectively). LAD CFR demonstrated a significant linear correlation with velocity microvascular flow reserve (r = 0.92, p <0.0001) and flow microvascular flow reserve (r = 0.77, p <0.0001). In conclusion, CFR in the LAD, successfully evaluated by transthoracic Doppler echocardiography and MCE, is significantly decreased in patients with syndrome X and even more in those with angina pectoris and ST-segment depression during adenosine testing. Thus, noninvasive evaluation of CFR by echocardiography is feasible and provides information on the severity of microvascular impairment.